UNIVERSITY TEACHERS' SKILLS AND ROLES IN STUDENT CENTERED EDUCATION - Elena Ancuța SANTI; Gabriel GORGHIU (Studia Universitatis Babes-Bolyai, 2022)
In academic education, according to the regulations imposed by the Bologna Process, the student is placed in the center of the educational process, fully considering the trainee interests for deepening the knowledge and taking into account the own personality, as autonomous and responsible citizen. This paradigm attributes to student an active role, becoming in this sense a partner for teacher in the fulfilment of own training and professional development. Based on constructivist theory, student-centered education emphasizes the understanding, building and reconstructing of knowledge experiences, experimentation, reflective approach related to teaching-learning process, involving also the adaptation of the teaching methods to learners' interests and needs, creativity and innovation. The relationship between teacher and student has multiple values, it is based on respect and trust, in order to achieve common goals. Feedback has an important and relevant role in optimizing the educational process. In the current socio-economic and cultural context, amplified by the effects of the pandemic, the rate of school leaving becomes high, which implies the adoption of effective measures for students to benefit from support, help, counseling and guidance. In addition to their roles required by student-centered education, teachers must express more openness, flexibility, ability to adapt to online constraints and understand the students' needs. The paper aims to identify the expectations that students have in relation to university teachers and to design a teacher's skills pattern in the actual context. For this purpose, 245 students from Valahia University of Targoviste, enrolled in the Teacher Training Department programs have been interviewed and asked to express their expectations, attitudes and perceptions about their teachers.